Adjuvant immunotherapy in resected early non-small cell lung cancer—battle lost, hopefully not the war! - Jeremic, Branislav; Cihoric, Nikola; Dubinsky, Pavol; Filipovic, Nenad (Journal of Thoracic Disease, 2016)
Lung cancer is major cancer killer in both sexes (1). In spite of improvements in diagnostic and therapeutic efforts in recent decades, still only a vast minority of patients with non-small cell lung cancer (NSCLC) undergo surgery. In these patients, additional chemotherapy (CHT) is considered a standard of care worldwide (2). Unfortunately, in spite of the lowest possible T and/or N burden of the disease, many people experience relapse, leading to a 5-year survival rates which range from more than 70% for stage IA to less than 25% in stage IIIA NSCLC (3). It is, therefore, not surprising that many efforts have been attempted to improve these figures. Building on recent success of drug therapy in advanced disease, usually labeled as targeted agents, some studies investigated adjuvant use of drugs such as erlotinib or gefitinib, but failed to demonstrate superiority over existing standards of care (4,5). Besides studies which showed the failure of tyrosine kinase inhibitors (TKIs), there were studies investigating the use of the DNA repair marker ERCC1 in adjuvant setting of NSCLC. While initial results were optimistic (6), more recent results were disappointing, leading to suggestion to abandon this research pathway (7-10).